2012
DOI: 10.5271/sjweh.3291
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of employment among cancer survivors after medical rehabilitation – a prospective study

Abstract: Objectives This study aimed to (i) investigate cancer survivor's employment status one year after the completion of a medical rehabilitation program and (ii) identify demographic, cancer, and psychosocial, treatment-, and work-related predictors of return to work (RTW) and time until RTW.Methods A total of 1520 eligible patients were consecutively recruited on average 11 months post diagnosis and assessed at the beginning (t 0 ) (N=1148) and end of rehabilitation (t 1 ) (N=1060) and 12 months after rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
0
34

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 124 publications
(154 citation statements)
references
References 47 publications
9
101
0
34
Order By: Relevance
“…This suggests that patients' own judgement can be used as a predictor of RTW. This is consistent with a study by Mehnert and Koch [23] who found that patients' intention to return to work at the beginning of cancer rehabilitation was a significant predictor of RTW at 1 year follow-up. Education showed a strong positive association with work ability (WAI) and a trend of being associated with higher RTW rates after 6 months, but not after 12 months.…”
Section: Discussionsupporting
confidence: 82%
“…This suggests that patients' own judgement can be used as a predictor of RTW. This is consistent with a study by Mehnert and Koch [23] who found that patients' intention to return to work at the beginning of cancer rehabilitation was a significant predictor of RTW at 1 year follow-up. Education showed a strong positive association with work ability (WAI) and a trend of being associated with higher RTW rates after 6 months, but not after 12 months.…”
Section: Discussionsupporting
confidence: 82%
“…Most studies using this model have examined development of work-related disorders or worker performance or work productivity; few have examined work disabilityEmployment after liver transplantation: a review [86]Cancer and work model [25]This evidence-based model includes work environment and demands factors, as well as function and health variables. Four outcomes are addressed including return to work, work ability, work performance, and sustainability (retention)Predictors of employment among cancer survivors after medical rehabilitation: a prospective study [87] …”
Section: Conceptual Framework Guiding Researchmentioning
confidence: 99%
“…Consequently, the options of returning to work and continuing employment during and after treatment have become realistic goals (Hoffman, 2005;Rowland, Aziz, Tesauro, & Feuer, 2001). The majority of cancer patients are willing and keen to return to work or to be reemployed (Mehnert & Koch, 2013;Taskila & Lindbohm, 2007;Hoffman, 2005). Return-to-work rates of 67%, 75%, and 84% respectively have been reported in various studies (Bradley & Bednarkek, 2002;Short, Vasey, & Tuncell, 2005;Brooks, 2009).…”
Section: Introductionmentioning
confidence: 96%